An immobilized liquid interface prevents device associated bacterial infection in vivo. (January 2017) - Chen, Jiaxuan; Howell, Caitlin; Haller, Carolyn A.; Patel, Madhukar S.; Ayala, Perla; Moravec, Katherine A.; Dai, Erbin; Liu, Liying; Sotiri, Irini; Aizenberg, Michael; Aizenberg, Joanna; Chaikof, Elliot L.
Abstract: Virtually all biomaterials are susceptible to biofilm formation and, as a consequence, device-associated infection. The concept of an immobilized liquid surface, termed slippery liquid-infused porous surfaces (SLIPS), represents a new framework for creating a stable, dynamic, omniphobic surface that displays ultralow adhesion and limits bacterial biofilm formation. A widely used biomaterial in clinical care, expanded polytetrafluoroethylene (ePTFE), infused with various perfluorocarbon liquids generated SLIPS surfaces that exhibited a 99% reduction in S . aureus adhesion with preservation of macrophage viability, phagocytosis, and bactericidal function. Notably, SLIPS modification of ePTFE prevents device infection after S . aureus challenge in vivo, while eliciting a significantly attenuated innate immune response. SLIPS-modified implants also decrease macrophage inflammatory cytokine expression in vitro, which likely contributed to the presence of a thinner fibrous capsule in the absence of bacterial challenge. SLIPS is an easily implementable technology that provides a promising approach to substantially reduce the risk of device infection and associated patient morbidity, as well as health care costs.